Analisis Preferensi Konsumen Terhadap Minat Beli Produk Wedang Herbal: (Studi Kasus CV X Kabupaten Magelang) - Khoirima, Siva; Khoiriyah, Annisa; Prayoga, Adi (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to determine consumer preferences for Wedang Herbal products and to identify attributes that influence purchasing interest based on consumer preferences. This research method is descriptive quantitative using a sampling technique carried out by non-probability sampling with a purposive sampling type. This study used 50 respondents with the criteria for respondents required are someone who has bought it and prospective consumers who will buy Wedang Herbal at CV X Magelang Regency. The data analysis method used to determine consumer preferences is conjoint analysis while to determine consumer purchasing interest using multiple linear regression analysis with the SPSS application program analysis tool. The results of the analysis show that consumer preferences have a significant effect on purchasing interest in Wedang Herbal products, both simultaneously (F test) and partially (t test).